PENERAPAN PSIKOEDUKASI TENTANG PENGETAHUAN KESIAPAN SEKOLAH ANAK TERHADAP IBU UNTUK MENINGKATKAN KEMANDIRIAN ANAK - Asiyah, nur; Mauliyah, Anita (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
The importance of mother's skills towards children is needed so that children become independent. In this case, efforts are needed to improve maternal parenting skills. One of the efforts that can be done is the provision of psychoeducation about knowledge of school readiness for mothers. Therefore, this study aims to determine whether there is an effect of child independence after the mother is given knowledge about psychoeducation. The mothers who were given the knowledge about Psychoeducation were 30 people who were the guardians of Hasanuddin Kindergarten students. The research data was collected with a focus on the children's independence scale and school readiness scale, because the research data was not normally distributed, the data analysis used in this study was Non Parametic Wilcoxson. From the results of the analysis, the value of t count is 0.015 and the value of sig. of 0.988 which means that there is no difference in the independence of the child before the mother is given psychoeducation and after being given psychoeducation.